Bioresources and bioprocess in biotechnology. Volume 2, Exploring potential biomolecules - Sugathan, Shiburaj ; Pradeep, N. S. ; Abdulhameed, Sabu (Springer, 2020)
This book is a compilation of detailed articles on various products and services that can be derived from bioresources through bioprocess. It offers in-depth discussions and case studies on commercially and therapeutically important enzymes, antimicrobials, anti-cancer molecules and anti-inflammatory substances. It also includes a separate section on emerging trends in bioactive substances research. This unique book is a valuable source of information for biotechnologists and bioprocess experts as well as academics and researchers who are actively involved in product and process development.